The Effect of Online Customer Reviews, Influencer Marketing, and Website Quality on Online Purchase Decisions at Shopee with Consumer Trust as A Mediation Variable - Rochmattunisa Rochmattunisa; Edy Purwo Saputro (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This research investigates the impact of Online Customer Reviews, Influencer Marketing, and Website Quality on online purchasing behavior at Shopee, with Consumer Trust acting as a mediating variable. Using a quantitative methodology, data were collected from 120 Shopee users in Indonesia via an online survey and subsequently analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that Online Customer Reviews, Influencer Marketing, and Website Quality exert positive, statistically significant effects on both purchasing decisions and consumer trust. Furthermore, consumer trust demonstrates a considerable positive influence on purchasing decisions and mediates the connection between all independent variables and purchasing decisions. These results underscore the pivotal role of trust in enhancing the efficacy of digital marketing strategies. From a practical perspective, the research recommends that e-commerce platforms prioritize authentic customer reviews, credible influencers, and high-quality websites to foster consumer trust and stimulate online purchasing behavior.